PELATIHAN PEMBUATAN OLAHAN KRIPIK SUKUN BAGI MASYARAKAT DESA GEJUGAN DALAM MENINGKATKAN KUALITAS PRODUK - Komar, Abd.; Yunus, Moch (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstrak Breadfruit is available very much and found in some villages in the District Pajarakan, especially in the Village of Gejugan District Pajarakan Probolinggo Regency. The business group Tani Sumber Jaya in developing a business kripik sukun available in the village, the Business Sumber Jaya have some problems in developing a business that equipment pembuatann product, is limited in the field of skills and knowledge in the process of Breadfruit Chips. The purpose of this activity in order to improve the economy of the Village community Gejugan and can also reduce the level of unemployment of youth around. The method implemented by developing the quality of the products, skills creative and innovate with using technology that is very appropriate, draining, and packaging of the product processed breadfruit. Therefore, it is necessary to develop products processed breadfruit and improved quality. The result shows if the use of technology then the results and quality will be increased, and the durability of the product processed from the breadfruit is guaranteed Keywords: Olahan Kripik Sukun, The Quality Of The Product